The Allelopathic Activity of Extracts and Isolated from Spirulina platensis - Charoenying, Patchanee; Laosinwattana, Chamroon; Chotsaeng, Nawasit (My University, 2022)
We determined the allelopathic effects of crude organic (hexane, ethyl acetate, and methanol) extracts of the cyanobacterial Spirulina platensis on barnyardgrass (Echinochloa crus-galli (L.) Beauv.) and Chinese amaranth (Amaranthus tricolor L.). The crude ethyl acetate extract showed the highest inhibitory activity and was subsequently fractionated by column chromatography into 23 fractions based on thin-layer chromatography band pattern similarities. Four concentrations (2000, 1000, 500, and 250 ppm) of each fraction were tested for their allelopathic activity. Fractions E6 and E13 exhib-ited the most significant inhibitory effects against Chinese amaranth. The constituents of the highly active E6F3-E6F5 fractions determined by GC-MS, chromatography, and spectroscopy included the fatty acids, γ-linolenic acid 15, oleic acid 12, and predominantly palmitic acid 7; minor constituents included 2-ethyl-3-methylmaleimide 9 and C11 norisoprenoids (dihydroactinidiolide 10 and 4-oxo-β-ionone 13). Isolation of E13 fraction by column chromatography revealed four C13 norisoprenoids: 3-hydroxy-β-ionone 17, 3-hydroxy-5α,6α-epoxy-β-ionone 18, 3-hydroxy-5β,6β-epoxy-β-ionone 19, and loliolide 20. Their structures were elucidated by NMR spectroscopy. All six isolated noriso-prenoids inhibited seed germination and seedling growth of Chinese amaranth at concentrations of 250–1000 ppm. Allelochemicals from S. platensis could be utilized in the development of novel bioactive herbicides.
Keywords: allelochemical; allelopathic effects; barnyardgrass; Chinese amaranth; cyanobacteria; Spirulina platensis; weeds